Development of the Everyday Life Rehabilitation model for persons with long-term and complex mental health needs: Preliminary process findings on usefulness and implementation aspects in sheltered and supported housing facilities - Lindström, Maria (Frontiers in Psychiatry, 2022)
This paper describes the initial phases of the design and development of the Everyday Life Rehabilitation (ELR) intervention, and it presents preliminary findings on usefulness and implementation aspects derived from an ongoing larger trial exploring the effect, cost-effectiveness, and usefulness of ELR. ELR is a model designed to meet the absence of meaningful activities and challenges with integrated, activity- and recovery-oriented rehabilitation in sheltered and supported housing facilities for persons with extensive psychiatric disabilities. The aim of the present study was to examine early experiences of implementing the ELR model from the perspectives of managers, housing staff, and occupational therapists. The paper will sum up preliminary findings based on process data included in an internal pilot prior to a full-scale pragmatic clustered RCT. Four Swedish municipalities with 19 housing facility units were involved and provided process data for the study. Thematic analysis were applied. The informants perceived the methodology to be well suited to the target group and context and to contribute to positive changes in participants' lives. The web-based training was also experienced as relevant and easily accessible to staff, as well as elements of collegial learning and feedback. However, they reported that their municipalities lacked basic conditions for making the whole concept work in such a short time. The ELR is overall perceived as useful, but experiences also make complex difficulties visible regarding integrated, coordinated rehabilitation and organizational readiness. Based on findings, a recommendation on basic prerequisites will be added to the ELR guidance for leadership and management. Clinical trial registration [ClinicalTrials.gov, 24 September 2021], identifier [NCT05056415].